The vertical recycled concrete aggregate filter for removal of phosphorus in wastewater - Abd Roni, N.; Adnan, S. H.; N Hamidon, N Hamid; T. Ismail, T. N. H. (2021)
The irresponsible disposal of untreated wastewater into waters, soil and groundwater results in polluted water resources. Moreover, nutrients such as phosphorus have become culprits of concern in accelerating eutrophication. Besides, this issue could cause water poisoning and the degradation of recreational opportunities. Therefore, for justifying this problem, it is important to understand the quantity of phosphorus (P) flows by using recycled concrete aggregate (RCA) as filter materials. RCA used as a filter system has emerged as an alternative technology for phosphorus removal. This can overcome the problem of construction site waste by converting the waste into valuable products. Thus, this study aims to investigate the physical and chemical characteristics of RCA that influenced adsorption of P and the percentage of phosphorus removal from synthetic wastewater by using two different sizes of RCA. A total of five vertical recycled concrete aggregate filter was designed. The samples taken from influent and effluent were tested once a week and analyzed to determine pH and percentage removal phosphorus. RCA was analyzed using Scanning Electron Microscopy (SEM) and Energydispersive X-ray spectroscopy (EDX) testing to determine chemical composition. The results show that RCA primarily contained aluminium, calcium, and magnesium that could enhanced the phosphorus adsorption. The RCA with size 5 to 10 mm is shown to have high potential to remove phosphorus up to 99.57%. The higher the size of RCA, the higher percentage of phosphorus removal. In conclusion, RCA has the potential to remove phosphorus from wastewater.